2009
DOI: 10.3390/molecules14125298
|View full text |Cite
|
Sign up to set email alerts
|

Protecting-Group-Free Synthesis of 2-Deoxy-Aza-Sugars

Abstract: The protecting-group-free asymmetric synthesis of 1,2,4-trideoxy-1,4-imino-L-xylitol is readily achieved in five steps from 2-deoxy-D-ribose and with an overall yield of 48%. Key in this synthesis is the application of our recently developed Vasella-reductive amination and carbamate annulation methodologies to the synthesis of 2-deoxy-aza-sugars. The carbamate annulation occurred with excellent yield and diastereoselectively (>20:1 d.r.), in favour of the 3,4-cis isomer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 29 publications
3
22
0
Order By: Relevance
“…In addition, two methylene protons were at different chemical shifts due to the chiral carbon C-12. Thus, the connection of the branch was confirmed as shown in Figure 2, because ½α 20 D was -33 (c 0.23, MeOH), which was the same specific rotation with the known similar compound (S)-5-amino-pent-1-en-3-ol hydrochloride [48]. As reported, the specific rotation direction of the sidechain was the same with the side-chain attached to the purine ring [49,50].…”
Section: Resultssupporting
confidence: 76%
“…In addition, two methylene protons were at different chemical shifts due to the chiral carbon C-12. Thus, the connection of the branch was confirmed as shown in Figure 2, because ½α 20 D was -33 (c 0.23, MeOH), which was the same specific rotation with the known similar compound (S)-5-amino-pent-1-en-3-ol hydrochloride [48]. As reported, the specific rotation direction of the sidechain was the same with the side-chain attached to the purine ring [49,50].…”
Section: Resultssupporting
confidence: 76%
“…While we envisioned that base‐mediated hydrolysis would readily allow for the synthesis of pyrrolidine I from carbamate II , it was not known if the formation of carbamate II, which could in principle be achieved via an I 2 ‐mediated carbamate annulation from alkenylamine III , would be stereoselective. Previously, we demonstrated that the carbamate annulation is highly 4,5‐ cis stereoselective for pyrrolidines without a substituent at the 2‐position,,, however our syntheses of amino‐imino‐hexitols using protecting groups, revealed that the stereochemistry of the 2‐substituent can affect the stereochemical outcome of the annulation. Others have also revealed that steric effects can influence the outcome of related electrophilic cyclisations .…”
Section: Introductionmentioning
confidence: 77%
“…28 We have previously reported on the preparation of 1,4-dideoxy-1,4-imino-D-xylitol (1) (57% total yield), 1,2,4-trideoxy-1,4-imino-L-xylitol (3) (48% total yield) and 1,4-dideoxy-1,4-imino-L-lyxitol (5) (55% total yield). 15,16 Again, all three syntheses were performed in five steps and with the highest reported yields to date.In addition to the high yields and short number of linear steps, another remarkable feature of our strategy is the high degree of diastereoselectivity observed in the carbamate annulation reaction. The reaction favours the formation of the 2,3-cis pyrrolidine, with the stereochemistry at the 3-position exerting stereocontrol on the cyclisation.…”
Section: Resultsmentioning
confidence: 99%
“…In the work presented herein, we report on the applicability of our novel protecting group free strategy 15,16 to the synthesis of Lxylitol 2 and D-lyxitol 4 and provide an explanation for the remarkable diastereoselectivity observed in our carbamate annulation methodology. Our efforts to improve the overall protecting group free strategy via the implementation of more environmentally favourable reductive amination protocols will also be presented.…”
Section: Introductionmentioning
confidence: 96%